Individual-, Family-, Community-, and Policy-Level Impact of a School-Based Cardiovascular Risk Detection Screening Program for Children in Underserved, Rural Areas: The CARDIAC Project. (5th June 2013) - Cottrell, Lesley; John, Collin; Murphy, Emily; Lilly, Christa L.; Ritchie, Susan K.; Elliott, Eloise; Minor, Valerie; Neal, William A.
Abstract : The Coronary Artery Risk Detection In Appalachian Communities (CARDIAC) Project has screened more than 80, 000 children (10–12 years) for cardiovascular and diabetes risk factors over the past 15 years. Simultaneous referral and intervention efforts have also contributed to the overall program impact. In this study, we examined evidence of programmatic impact in the past decade at the individual, family, community, and policy levels from child screening outcomes, referral rates, participation in subsequent services, and policies that embed the activities of the project as a significant element. Within this period of time, fifth-grade overweight and obesity rates were maintained at a time when rates elsewhere increased. 107 children were referred for additional screening and treatment for probable familial hypercholesterolemia (FH); 82 family members were subsequently screened in family-based screening efforts. 58 grants were distributed throughout the state for community-appropriate obesity intervention. A state wellness policy embedded CARDIAC as the method of assessment and national child cholesterol screening guidelines were impacted by CARDIAC findings. The sustainability and successful impact of this school-based program within a largely underserved, rural Appalachian state are also discussed.